IN VITRO ASSESSMENT OF LONG-TERM EFFECTS OF CYTOTOXIC DRUGS ON MALE REPRODUCTIVE FUNCTION - T. G. Borovskaya; V. E. Goldberg; M. E. Poluektova; Yu. A. Shchemerovа; A. V. Vychuzhanina; V. A. Grigoreva; O. V. Kollantay; S. I. Kamalova (Сибирский онкологический журнал, 2020)
The purpose of the study was a comparative assessment of long-term toxic effects of cytotoxic drugs (anthracycline antibiotics, topoisomerase activity inhibitors, platinum and taxane complex compounds) on male reproductive function. Material and methods. 2.5-month-old male Wistar rats were used in the experiment. The following cytotoxic drugs were administered to animals in the maximum tolerated dose: Vepesid (etoposide, Teva, Israel), Irinotecan (Campto, Rhone-Poulens, Great Britain), Carboplatin (kemokarb, Dabur India Ltd., India), Paclitaxel (mitotax, Dr. Reddy`s, India), Platidiam (Lachema, Czech Republic), Pharmorubicin (Farmitalia, Carlo Erba). The reproductive status was assessed 90 and 180 days after administration of cytotoxic drugs. The fertilizing ability, productivity of spermatogenesis and the viability of a fertilized egg were evaluated. To determine the sensitivity of different types of spermatogonia to the drugs, we studied the dynamics of the number of their cell populations 2, 5, 10, 15, 30, 90 and 180 days after starting the experiment. Results. In long-term follow-up following administration of farmorubicin and paclitaxel to male rats, a complete (pharmacorubicin) or partial (paclitaxel) decrease in the fertilizing ability due to oligospermia was detected. The decrease in spermatogenesis productivitywas reversible. In rats treated with topoisomerase activity inhibitors, the fertilizing ability was preserved, however spermatogenic failure was also seen, as judged by the total sperm number. In the long term after the administration of platinum complexes, no decline in the reproductive function was observed, and the spermatogenesis productivity corresponded to the control values. The severity of toxic effects on gonads was determined by the sensitivity of different types of spermatogonia to the action of drugs. Pharmorubicin and paclitaxel exerted a pronounced toxic effect on stem spermatogonial cells. Paclitaxel and carboplatin induced dominant lethal mutations in spermatogonia, but the likelihood of gametes bearing genetic damage incompatible with life decreased over time.